Correlation factors and demographic characteristics on homebuyer’s purchase decision amid covid-19 pandemic at Pasir Gudang, Johor - Lee, Wee Haw (2022)
Property residential market occurs the property overhang and property project delay issues amid the Covid-19 pandemic. In this research, the aim is to determine the correlation between the homebuying factors and demographic characteristics on the homebuyer’s purchase decision amid the Covid-19 pandemic. Hence, there are three research objective which are to determine the homebuying factors that influence homebuyer’s purchase decision during the Covid-19 pandemic, to investigate the demographic characteristics of residential homebuyers that influence their purchase decisions during period of Covid-19 pandemic and to evaluate the relationships between the homebuying factors and the demographic characteristics of residential property during period of Covid-19 pandemic. The method of data collection used is questionnaire distribution, the result had been composed and analyses the feedback and opinions from the residents who are the house owners and the potential buyers who are planning to purchase houses at Pasir Gudang, Johor. Then, the data analysis method are using linear logistic regression and multivariate analysis of variance. The results findings shows that homebuyer’s purchase decision are influenced by all homebuying purchase factors amid Covid-19 pandemic which are the significant variables are hospital & clinics workplace, schools, down payment, monthly payment EPF Withdrawal , quality of property, build-up area, security & safety and air quality. The findings illustrate that homebuyer’s purchase decision are influenced by gender, education level, occupation, family income and family size amid Covid19 pandemic. The findings of this research have implications for the academic literature as they specifically extend on homebuying factors of homebuyers and demographic characteristics of residential homebuyers for the broader exploration of the efforts to develop housing development in Malaysia.